Changes in the Gut Metabolic Profile of Gestational Diabetes Mellitus Rats Following Probiotic Supplementation - Zheng, Qing-Xiang; Wang, Hai-Wei; Jiang, Xiu-Min; Ge, Li; Lai, Yu-Ting; Jiang, Xin-Yong; Huang, Ping-Ping; Chen, Fan; Chen, Xiao-Qian (Frontiers in Microbiology, 2022)
The roles of gut microbiota and metabolomics in women with gestational diabetes mellitus (GDM) are not well understood. This study investigated the gut metabolomic profiling of GDM rats and GDM rats treated with probiotic supplements. Associations between gut metabolites and microbiota were also studied in GDM rats. Liquid chromatography-mass spectrometry was used to detect gut metabolites in GDM rats and GDM rats treated with probiotic supplements of 0.5 gram (low-dose group) or 1 gram (high-dose group) for 15 days. Each gram of probiotic supplement contained 5 × 107 CFU of Lactobacillus rhamnosus LGG and 1×108 CFU of Bifidobacterium animalis subspecies lactis Bb12. The association between gut metabolites and microbiota in GDM rats was investigated using Spearman’s correlation. Finally, 10 rats in the normal pregnant group, eight rats in the GDM model group, eight GDM rats in the low-dose probiotics group, and nine GDM rats in the high-dose probiotics group were further studied. Serum parameters and, pancreatic and colon histology were significantly changed in GDM rats and these were restored using probiotic supplements. In total, 999 gut metabolites were detected in the feces, and GDM rats were distinguished from normal rats. The levels of 44 metabolites were increased in GDM rats, and they were alleviated using probiotic supplements. Changes in metabolites in GDM rats were associated with amino acids and bile acids metabolism signaling pathways. Furthermore, changes in metabolites after probiotic supplementation were associated with porphyrin and chlorophyll metabolism pathways. We found that the Allobaculum genus displayed strong positive correlations, while the Bryobacter and Gemmatimonas genera displayed strong negative correlations with metabolisms of amino acid and bile acids in GDM rats. The Lactobacillus and Bifidobacterium genera were positively correlated with gut metabolites. Overall, our results showed that metabolism signaling pathways of amino acid and bile acids are associated with the development of GDM. Probiotic supplements alleviate the pathology of GDM through the metabolism pathways of amino acids, bile acids, porphyrin, and chlorophyll.